Obesity Attenuates Ventilator-Induced Lung Injury by Modulating the STAT3–SOCS3 Pathway - Wu, Shih-Wei; Peng, Chung-Kan; Wu, Shu-Yu; Wang, Yu; Yang, Sung-Sen; Tang, Shih-En; Huang, Kun-Lun (Frontiers in Immunology, 2021)
Background: Ventilator-induced lung injury (VILI) is characterized by vascular barrier dysfunction and suppression of alveolar fluid clearance (AFC). Obesity itself leads to chronic inflammation, which may initiate an injurious cascade to the lungs and simultaneously induce a protective feedback. In this study, we investigated the protective mechanism of obesity on VILI in a mouse model. Methods: The VILI model was set up via 6-h mechanical ventilation with a high tidal volume. Parameters including lung injury score, STAT3/NFB pathway, and AFC were assessed. Mice with diet-induced obesity were obtained by allowing free access to a high-fat diet since the age of 3 weeks. After a 9-week diet intervention, these mice were sacrificed at the age of 12 weeks. The manipulation of SOCS3 protein was achieved by siRNA knockdown and pharmaceutical stimulation using hesperetin. WNK4 knockin and knockout obese mice were used to clarify the pathway of AFC modulation. Results: Obesity itself attenuated VILI. Knockdown of SOCS3 in obese mice offset the protection against VILI afforded by obesity. Hesperetin stimulated SOCS3 upregulation in nonobese mice and provided protection against VILI. In obese mice, the WNK4 axis was upregulated at the baseline, but was significantly attenuated after VILI compared with nonobese mice. At the baseline, the manipulation of SOCS3 by siRNA and hesperetin also led to the corresponding alteration of WNK4, albeit to a lesser extent. After VILI, WNK4 expression correlated with STAT3/NFB activation, regardless of SOCS3 status. Obese mice carrying WNK4 knockout had VILI with a severity similar to that of wild-type obese mice. The severity of VILI in WNK4-knockin obese mice was counteracted by obesity, similar to that of wild-type nonobese mice only. Conclusions: Obesity protects lungs from VILI by upregulating SOCS3, thus suppressing the STAT3/NFB inflammatory pathway and enhancing WNK4-related AFC. However, WNK4 acitvation is mainly from direct NFB downstreaming, and less from SOCS3 upregualtion. Moreover, JAK2–STAT3/NFB signaling predominates the pathogenesis of VILI. Nevertheless, the interaction between SOCS3 and WNK4 in modulating VILI in obesity warrants further investigation.